Isoetes vanensis (Isoetaceae) sp nov from Turkey - (:unkn) unknown (MAGNOLIA PRESS, 2016)
A previously undescribed species, Isoetes vanensis, is described and illustrated. Isoetes vanensis is distinguished from allied species by its papery scales and small megaspores bearing a low tuberculate texture and a fimbriate-ecuelate micro-ornamentation. A table of comparative diagnostic characters and character states for I. vanensis and allied taxa, a geographic distribution map, and SEM images of megaspores and microspores showing ornamentation patterns are included.
Keywords: new species; Isoetes; Isoetaceae; Turkey; LYCOPHYTA